2012
DOI: 10.1097/ta.0b013e31821a416a
|View full text |Cite
|
Sign up to set email alerts
|

Physical effects of trauma and the psychological consequences of preexisting diseases account for a significant portion of the health-related quality of life patterns of former trauma patients

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…The remainder were retrospective studies (n = 6751). Collectively the studies were conducted in different countries and continents: Seven in the USA [29][35]; six in Australasia (four in Australia and two in New Zealand) [36]–[41]; 19 in Europe (five in Germany [27], [42][45], four each in The Netherlands [46][49] and Norway [8], [9], [50], [51], two each in the UK [24], [25] and Sweden [28], [52], one each in Switzerland [53], Denmark [26] and one each in Israel [54] and South Africa [55] (Table 1, Table S3). …”
Section: Resultsmentioning
confidence: 99%
“…The remainder were retrospective studies (n = 6751). Collectively the studies were conducted in different countries and continents: Seven in the USA [29][35]; six in Australasia (four in Australia and two in New Zealand) [36]–[41]; 19 in Europe (five in Germany [27], [42][45], four each in The Netherlands [46][49] and Norway [8], [9], [50], [51], two each in the UK [24], [25] and Sweden [28], [52], one each in Switzerland [53], Denmark [26] and one each in Israel [54] and South Africa [55] (Table 1, Table S3). …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous studies found that physical wellbeing was further decreased after the trauma than mental wellbeing 5;8 but that the overall decrease in HRQOL remained and primarily had a psychological basis. 5 Future studies should follow patients over time to determine how physical limitations and psychological complaints develop over time while investigating how these factors influence each other.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the (HR)QOL of severely injured patients is lower than that of the general population. [2][3][4][5][6][7][8] This decrease in (HR)QOL seems to depend on both psychological complaints and physical limitations, but few studies measured these three parameters within the same study population.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found psychological problems after injury can have a greater impact on quality of life than the physical injury [4, 10, 17, 18] and impairments to quality of life can persist after resolution of the psychological symptoms [19]. Few studies have focussed on the relationship between psychological morbidity and quality of life after injury amongst general injury populations, including those with minor and more major injuries [4, 16, 20, 21]. Identifying and managing psychological problems are recognised as an important component of UK post-injury care for major trauma [22] or for specific injuries such as burns [23], head injuries [24] or spinal cord injuries [25].…”
Section: Introductionmentioning
confidence: 99%